The Application Of Inclined Field Media to The Level of Anxiety In Learning Outcomes Of Forward Roll Movements - Mahadevi, Nadya Emily; Indriarsa, Nanang (Sekolah Tinggi Olahraga dan Kesehatan Bina Guna, 2024)
Forward roll movement is one of the materials that exists in the learning of Physical Education. However, there were many students who did not dare to do forward roll movement because of anxiety. The researchers used inclined field media to help reduce anxiety. The goal of this research is to find out how much the influence of the inclined field media in reducing the level of anxiety of the students. The approach used in this research is quantitative descriptive with a pre-experimental design one group pre-test posttest method. The results of the research showed that the pretest for the level of anxiety had an average score of 83.44, after given treatment the students obtained an average rating of 80.89. From the results of the treatment using the media of the inclined field, the student's anxiety rate decreased by 4% and the learning outcome of the student also improved. The anxiety level of 11th-grade students from SMAN 21 Surabaya, specifically in the IPA 3 class, towards forward roll learning, is included in the medium category. As for the learning outcomes, the pretest scores for the forward roll were an average of 65.28, while after the treatment, students achieved an average score of 76.67. Therefore, students experienced an 18% improvement in learning outcomes.